HAHN. Lewis Edwin (Ed.): The Philosophy of Hans-Georg Gadamer, The Library of Living Philosophers, Vol. XXIV, Chicago and La Salle, Illinois: Open Court, 1997, 619 pp. - Quintanilla, Pablo (1997)
No contiene resumen